Black moon - Russell, Romina (Russell, Romina. Zodiac novel, 2016)
Believing the Marad terrorist group is still out there in spite of peace efforts throughout the Zodiac Galaxy, Rho joins a new political party before discovering horrifying links between the party and her late mother.